2013
DOI: 10.1016/j.childyouth.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and substance use disorders among foster youth transitioning to adulthood: Past research and future directions

Abstract: At a time when there is increasing attention being given to systematically integrating the well-being of children with the goals of safety and permanence in child welfare, little is known about the psychosocial functioning of foster youth transitioning to adulthood from substitute care. This article systematically reviews 17 peer-reviewed articles and/or research reports to identify lifetime and past year prevalence rates of mental health disorders and service utilization. At ages 17 or 18, foster youth are 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(95 citation statements)
references
References 71 publications
(94 reference statements)
6
89
0
Order By: Relevance
“…5 Despite transitioning youths' high level of need, they experience significant challenges to accessing mental health services when aging out of foster care. [2][3][4][5][6] Mental health care utilization declines substantially during the transition period. 6,7 Mental health service discontinuity in youth aging out of foster care has been found to be mediated by insurance status, and several other sociodemographic characteristics, including age of exit from foster care, race/ ethnicity, gender, and geographic location.…”
Section: What's Newmentioning
confidence: 98%
See 1 more Smart Citation
“…5 Despite transitioning youths' high level of need, they experience significant challenges to accessing mental health services when aging out of foster care. [2][3][4][5][6] Mental health care utilization declines substantially during the transition period. 6,7 Mental health service discontinuity in youth aging out of foster care has been found to be mediated by insurance status, and several other sociodemographic characteristics, including age of exit from foster care, race/ ethnicity, gender, and geographic location.…”
Section: What's Newmentioning
confidence: 98%
“…1 Youth aging out of foster care have disproportionately higher levels of mental health problems compared with youth in the general population. [2][3][4] They also are at risk for many negative outcomes after transition from foster care to independent living in adulthood, including poor educational attainment, unemployment, early pregnancy, and homelessness, which might further exacerbate existing mental health problems. 5 Despite transitioning youths' high level of need, they experience significant challenges to accessing mental health services when aging out of foster care.…”
Section: What's Newmentioning
confidence: 98%
“…They are not able to achieve optimal level of subjective well-being and will also have a relatively low quality of life (Eid & Diener, 2004). Furthermore, they have a high risk of psychological problems (Havlicek et al, 2013;Hawkins et al, 2000;Metzler et al, 2007;Southerland et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Adolescents are faced with various demands and expectations from either the environment or themselves hence when they are unable to comply, psychological problems will occur (Havlicek et al, 2013;Metzler et al, 2007;Hawkins et al, 2000). Inability to forgive and forget mistakes or disappointments that cause domination of negative affect over positive can lead to low levels of subjective well-being (McCullough, Bellah, Kilpatrick, & Johnson, 2001;McCullough, 2000;McCullough et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This is almost five times higher than the rate for adolescents living in private households (Green et al, 2005). Relatedly, in a US study (Havlicek et al, 2013), young people in foster care aged 17 or 18 were two to four times more likely to experience lifetime and/or past year mental health problems compared to young people in the general population of a similar age. Another US study (Petrenko et al, 2011) identified 22% of children in an out-ofhome cohort had unmet mental health needs.…”
Section: Mental Health Of Maltreated Youthmentioning
confidence: 74%